(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
The article studies the philosophical significance of using educational methods in forming a culture of communication among young people. It reveals the importance of using educational methods in forming a culture of communication among young people, their significant contribution to their success and respect in social life, and the importance of pedagogical methods, the general participation of parents and society in achieving this goal.